2007
DOI: 10.1016/j.apmr.2007.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Models for Physical Capacity at Discharge and 1 Year Postdischarge From Rehabilitation in Persons With Spinal Cord Injury

Abstract: ABSTRACT. Haisma JA, van der Woude LH, Stam HJ, Bergen MP, Sluis TA, de Groot S, Dallmeijer AJ, Bussmann JB. Prognostic models for physical capacity at discharge and 1 year postdischarge from rehabilitation in persons with spinal cord injury. Arch Phys Med Rehabil 2007;88:1694-703.Objective: To develop prognostic models for physical capacity at discharge and 1 year after discharge from inpatient rehabilitation in persons with spinal cord injury (SCI).Design: Inception cohort; data collected at start of rehabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…33 While there have been few studies examining the physical capacity among adults with acute SCI, longitudinal investigations have revealed improvements both during inpatient rehabilitation and in 1 year post-discharge, especially among individuals with tetraplegia. 34 VO 2peak during rehabilitation also appears to be the best predictor of future VO 2peak 35 and is negatively associated with complications post-discharge. 36…”
Section: Physical Capacitymentioning
confidence: 93%
See 1 more Smart Citation
“…33 While there have been few studies examining the physical capacity among adults with acute SCI, longitudinal investigations have revealed improvements both during inpatient rehabilitation and in 1 year post-discharge, especially among individuals with tetraplegia. 34 VO 2peak during rehabilitation also appears to be the best predictor of future VO 2peak 35 and is negatively associated with complications post-discharge. 36…”
Section: Physical Capacitymentioning
confidence: 93%
“…evaluating peak physical capacity early in the rehabilitation process may assist with the development of rehabilitation goals. 35 The purpose of the first study was to describe the aerobic capacity, orthostatic tolerance, and exercise perceptions of adults with sub-acute SCI. It was predicted that there would be differences in physical capacity and the prevalence of orthostatic hypotension based on level of injury and that participants would have favourable opinions of exercise when discharged from inpatient SCI rehabilitation.…”
Section: Exercise Prescription For Individuals With Spinal Cord Injurymentioning
confidence: 99%
“…The lesions in these subjects severely disrupted the integration of the motor, sensory, and autonomic functions from below the level of the lesion, and obviously decreased functional ability and inevitably associated with an increased risk of complications. 1, [18][19][20][21] Medical complications are a frequent cause of morbidity and mortality, and lead to an increased rate of hospitalization, increased care cost, loss of employability, and decreased quality of life. 3,8 Cardenas et al 3 have indicated that the occurrence of medical complications plays an important role in the continuum of care for individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bland and Altman 17 the Student paired t-test that Vinet et al 19 used is irrelevant to the question of agreement since two measures designed to measure the same quantity will almost always be related. The Bland-Altman plot in the study of Haisma et al 12 showed that the estimated peak power output may be 20 W higher or lower than the observed outcome (mean AE SD: 45 AE 19 W). Since this model was not cross-validated, the discrepancies could be even larger.…”
Section: Discussionmentioning
confidence: 97%
“…11 Insight in the expected future wheelchair skills of an individual might assist physicians and health care professionals in setting realistic rehabilitation goals, monitoring and targeting specific interventions, and facilitate planning for post-discharge care. 12 When developing a prognostic model that gives an estimate for future wheelchair skills, it is important to choose predictors that are easily available for professionals, such as personal and lesion characteristics and baseline wheelchair skill scores. A previous study, 5 based on the same but smaller data-set as the present study (N ¼ 121), showed that personal and lesion characteristics are related to the course of wheelchair skill performance during and after inpatient rehabilitation.…”
Section: Introductionmentioning
confidence: 99%